GREEK AGRICULTURAL CO-OPERATIVES: LEGAL CONCEPTS AND TAX LEGISLATION AND TREATMENT - Fefes, Michael; Charitonidou, Marietta (International Journal of Cooperative Law, 2025)
Co-operatives have already been in Greek legal life for 106 years, since the first legal instrument on co-operatives was promulgated in 1915. Special attention is paid to the case of agricultural co-operatives, since it is themost familiar and “regulated” co-operative form. Moreover, the legislative regime concerning the tax treatment of agricultural co-operatives is particularly interesting, since its study provides us with valuable insight as to the general attitude of theGreek State and its legislature towards co-operative organization and operation with a special emphasis on the agricultural sector. Weattempt to gather and list all of the current issues specifically as to the taxation system of agricultural co-operatives inGreece, while presenting the historical background of co-operative legislation since 2000. There is a clarifying approach of the concepts of “surplus” and “profit” for agricultural co-operatives, an analysis of the current tax regime (income tax, VAT,etc.), its compliance with the EU competition and state aids provisions and a comparison between the taxation treatments of co-operatives with other capital based legal entities. Despite the fact that co-operative tax legislation is fragmented in severallaws, which were themselves repeatedly amended, modified, repealed or re-enacted, at the end of the day the reader shall have an overall view of the issue